2017
DOI: 10.1016/j.compscitech.2017.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Orientation-dispersed pseudo-ductile hybrid composite laminates – A new lay-up concept to avoid free-edge delamination

Abstract: a b s t r a c tMulti-Directional hybrid composites can suffer from free-edge delamination, a damage mode that doesn't exist in Uni-Directional hybrid composites and can hinder the pseudo-ductility that can be achieved with thin-ply hybrids. This paper presents a new lay-up concept called 'orientation-dispersed' laminates to avoid this mode of damage in quasi-isotropic hybrids. It is shown that the energy release rates at the free-edges of orientation-dispersed layups are significantly lower than those in 'orie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…In all the configurations, free edge delamination, an undesirable damage mode in previously investigated orientation-blocked hybrids [29], was successfully suppressed due to the orientation-dispersed design [30] that produces lower energy release rates at the free-edges of the laminates.…”
Section: Un-notched Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…In all the configurations, free edge delamination, an undesirable damage mode in previously investigated orientation-blocked hybrids [29], was successfully suppressed due to the orientation-dispersed design [30] that produces lower energy release rates at the free-edges of the laminates.…”
Section: Un-notched Resultsmentioning
confidence: 93%
“…Early work on pseudo-ductile composites [22][23][24][25][26][27][28] reported that by combining different types of thin-ply carbon fibres and standard glass fibres, an optimised gradual failure process can be achieved in tension that can avoid catastrophic failure. In these studies, unidirectional hybrids were used to generate pseudoductile behaviour, with the concept then applied on quasi-isotropic (QI) laminates [29][30][31]. It was found that by changing the relative and absolute thickness of the carbon layer as well as the material properties, three damage mechanisms, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24][25][26][27] The hybridization of different fibers is a successful approach to address the lack of the ductility in composites. 28 As reported by Fotouhi et al 29 and Jalalvand et al, 30 hybridization is one of the methods that can introduce gradual failure in composites and also can achieve more cost-effective materials. Mixing the fibers can be done in different levels such as intermingled continuous fibers, 31 intermingled aligned short fibers, 32 interlayer or sandwiched layers 33 and intralayer.…”
Section: Introductionmentioning
confidence: 92%
“…In this method, two types of plies with different fibers are co-cured to achieve a desired performance, and to produce a more cost-effective material [15,16]. Most of the work done to-date on hybrid composites has concerned hybrids under tensile [17,18], bending and compression loadings [19][20][21]. There are also some studies on hybrid composites when subjected to indentation and impact loadings [22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%